Common Features of Coronavirus and Influenza Pandemics and Surface Proteins of their Pathogens. Parallels - E. P. Kharchenko (Эпидемиология и вакцинопрофилактика)
Relevance. Coronaviruses and influenza viruses induce pandemics taking away many human lives and seeding social-economic chaos. Possibility to prognose pandemic features on characteristics of surface proteins of their pathogens is not investigated.Aim is to characterize the common features of the pandemic coronavirus S-protein and the pandemic virus influenza hemagglutinin in connection with the features of a coronavirus pandemic and influenza pandemics.Materials and method. For the bioinformatic analysis the protein sequences of pandemic coronavirus strains and pandemic influenza virus strains, influenza virus strains of 2017–2018 season and also influenza virus type B strains were used. In proteins an amino acid content, the sums of the charged amino acids and the.Results. It was found out that the increase of amount of the amino acids forming intrinsically disordered regions in the coronavirus S-protein S1 subunit and influenza virus H1 hemagglutinin HA1 subunit is characteristic of the pandemics with high morbidity and the increase of arginine and lysine with comparison with aspartic and glutamic acids in those proteins is peculiar to viruses inducing the pandemics with lower lethality.Conclusion. The features (morbidity and lethality) of the coronavirus pandemic and influenza virus pandemic are associated with the quantitative amino acids content of pandemic virus surface proteins.